2014
DOI: 10.5137/1019-5149.jtn.11314-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical outcomes of secondary epilepsy from hippocampal lesions: a report of 56 cases and literature review

Abstract: ABSTRACToperative methods in the treatment of secondary epilepsy from hippocampal lesions. █ MATERIAl and METhODS Selection of PatientsThere were 56 patients enrolled in this study including 31 males and 25 females. These patients were aged 16 to 74 years (mean age, 35.1±13.5 years) and had a history of epilepsy from 2 months to 10 years (mean length, 17.2±13.1 months). The inclusion criteria for patients diagnosed as having hippocampal sclerosis was that systematic anti- █ InTRODuCTIOnMesial temporal lobe epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Оценивая результаты хирургического лечения эпилепсии при поражениях гиппокампа в группе из 56 пациентов с разнообразными по гистологической структуре поражениями МБОВД, W. Jun и соавт. [31] подчеркнули, что хороший противоэпилептический эффект может быть достигнут с одинаковым успехом (1-й класс по Engel в 80-83% случаев) как при удалении только новообразования с прилежащей мозговой тканью, так и при значительной резекции височной доли, включающей и медиальные структуры. Результаты хирургического лечения эпилепсии у пациентов с КМ МБОВД в представленной нами группе показали необходимость удаления патологического новообразования с перифокальной глиотической тканью.…”
Section: Discussionunclassified
“…Оценивая результаты хирургического лечения эпилепсии при поражениях гиппокампа в группе из 56 пациентов с разнообразными по гистологической структуре поражениями МБОВД, W. Jun и соавт. [31] подчеркнули, что хороший противоэпилептический эффект может быть достигнут с одинаковым успехом (1-й класс по Engel в 80-83% случаев) как при удалении только новообразования с прилежащей мозговой тканью, так и при значительной резекции височной доли, включающей и медиальные структуры. Результаты хирургического лечения эпилепсии у пациентов с КМ МБОВД в представленной нами группе показали необходимость удаления патологического новообразования с перифокальной глиотической тканью.…”
Section: Discussionunclassified
“…Though several new antiepileptic drugs have emerged over the past years, the incidence of refractory epilepsy remains high and seizure freedom eludes many patients with epilepsy ( 3 5 ). Epidemiological data has indicated that more than twenty percent of newly diagnosed patients are translating into refractory epilepsy every year ( 6 , 7 ). Many factors affect the treatment of epilepsy including environmental factors and genetic factors ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%